Differential response of Scots pine seedlings to variable intensity and ratio of red and far‐red light. (21st April 2017) - Razzak, Abdur; Ranade, Sonali Sachin; Strand, Åsa; García‐Gil, M. R.
Abstract: We investigated the response to increasing intensity of red (R) and far‐R (FR) light and to a decrease in R:FR ratio in Pinus sylvestris L. (Scots pine) seedling. The results showed that FR high‐irradiance response for hypocotyl elongation may be present in Scots pine and that this response is enhanced by increasing light intensity. However, both hypocotyl inhibition and pigment accumulation were more strongly affected by the R light compared with FR light. This is in contrast to previous reports in Arabidopsis thaliana (L.) Heynh. In the angiosperm, A . thaliana R light shows an overall milder effect on inhibition of hypocotyl elongation and on pigment biosynthesis compared with FR suggesting conifers and angiosperms respond very differently to the different light regimes. Scots pine shade avoidance syndrome with longer hypocotyls, shorter cotyledons and lower chlorophyll content in response to shade conditions resembles the response observed in A . thaliana . However, anthocyanin accumulation increased with shade in Scots pine, which again differs from what is known in angiosperms. Overall, the response of seedling development and physiology to R and FR light in Scots pine indicates that the regulatory mechanism for light response may differ between gymnosperms and angiosperms. Abstract : We studied the response of Scots pine seedlings to variable intensity and ratio of red (R) and far‐R (FR) light with respect to hypocotyl elongation and accumulation of pigments, for example, chlorophyll and anthocyanin. The results showed that FR high‐irradiance response is present in pine, is enhanced by increasing light intensity and is more strongly affected by the R light compared with FR light. The overall response in pine is different from what is been previously reported in Arabidopsis or angiosperms; we conclude that the regulatory mechanism for light response may differ between gymnosperms and angiosperms.